Development of dance and movement therapy-based video media to cope with final year student thesis stress - Dewisagita Dewisagita; Laurentia Chezary T. P.; Rahmadiah Jessica E.; Rainissa Anindya (Indonesian Institute for Counseling, Education, and Therapy (IICET), 2022)
For college students, it turns out the thesis task is not an easy task. These difficulties make college students often despair of stress and cause them to not be able to complete their studies on time. Stress is the second most common problem felt by students. Dance and Movement Therapy is a therapy that uses movement and dance to support the body's intellectual, emotional, and motor functions. Emotionally dance enables the individual to have self awareness, reduces stress and is the best means that can be done to express emotional feelings. This research swants to see the effect of Dance and Movement Therapy assisted by AudioVisual-based educational media on the handling of stress thesis final level students. So this research aims to overcome the stress of thesis on students with the educational media used in this study. This research used research and development. This research was conducted on 25 college students who were undergoing a thesis period. The results of this study as a whole are less effective because researchers cannot ascertain whether the subject really follows the video from start to finish or not.